INFLUENCE OF GRAVITY MODULATION ON THE INITIATION OF DOUBLE DIFFUSIVE CONVECTION IN BOTH FLUID AND POROUS LAYER - Sidram, W.; Patil, Siddharama (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Linear stability analysis of convection in a binary fluid and saturated porous layer subjected to gravity modulation is performed. Regular perturbation method based on small amplitude of modulation is employed to compute onset threshold for synchronous mode, as a function of frequency, . The results of Darcy porous layer and fluid layer form the limiting cases of Brinkman porous layer. The gravity modulation exhibits both stabilizing and destabilizing effect in case of fluid layer while inhibits the porous layer convection. Since the onset of convection is affected by various parameters, by their proper tuning convection may be regulated.